2023
DOI: 10.3390/nu15051282
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Diet Quality and the Risk of Dementia in the Oldest Old

Abstract: This study examined the associations between overall diet quality and the risk of dementia in a rural cohort among the oldest old. Included in this prospective cohort study were 2232 participants aged ≥ 80 years and dementia-free at the baseline according to the Geisinger Rural Aging Study (GRAS), a longitudinal cohort in rural Pennsylvania. In 2009, diet quality was assessed by a validated dietary screening tool (DST). Incident cases of dementia during 2009–2021 were identified using diagnosis codes. This app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Malnutrition can lead to weight loss, muscle tissue loss, body wasting, and other physical frailties, ultimately contributing to the development of CF. Furthermore, the lack of essential nutrients such as serum proteins, vitamins, and trace elements can affect cognitive function, which is also a crucial factor in the development and progression of physical frailty and cognitive impairment [ 35 ]. Zupo et al found that malnourished elderly people with CF had a higher mortality rate [ 36 ], highlighting the urgent need to improve the nutrition status of patients with CF.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition can lead to weight loss, muscle tissue loss, body wasting, and other physical frailties, ultimately contributing to the development of CF. Furthermore, the lack of essential nutrients such as serum proteins, vitamins, and trace elements can affect cognitive function, which is also a crucial factor in the development and progression of physical frailty and cognitive impairment [ 35 ]. Zupo et al found that malnourished elderly people with CF had a higher mortality rate [ 36 ], highlighting the urgent need to improve the nutrition status of patients with CF.…”
Section: Discussionmentioning
confidence: 99%
“…A diet high in polyunsaturated fatty acids (PUFA) modifies the fibrillar/prefibrillar A oligomer ratio to reduce the density of hippocampal A plaques (the former is less toxic), thereby producing mild behavioral improvements in a transgenic rodent model of AD [61][62][63][64]. The fluidity of membranes and the activity of enzymes in neurons may be impacted by dietary intake of omega-3 and omega-6 PUFA and monounsaturated fatty acids (MUFA), which may then modify the architecture and functions of the brain [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…29 However, diet alone was not found to be protective against ADRD. 22,87 Socioeconomic factors: Higher education is believed to have neuroprotective effects, and such effects were observed in two out of three studies analyzing the association between education and ADRD risk. 88,89 However, the third study found no significant correlation.…”
Section: Psychiatric-related Interventionsmentioning
confidence: 99%